A prediction model for short-term neonatal outcomes in severe early-onset fetal growth restriction. (October 2019) - Sharp, Andrew; Jackson, Richard; Cornforth, Christine; Harrold, Jane; Turner, Mark A.; Kenny, Louise; Baker, Philip N.; Johnstone, Edward D.; Khalil, Asma; von Dadelszen, Peter; Papageorghiou, Aris T.; Alfirevic, Zarko
Abstract: Background: Severe early-onset fetal growth restriction (FGR) predisposes to fetal death, neonatal death, neonatal morbidity and neurodisability. The use of placental biomarkers has been proposed for risk stratification in pre-eclampsia, but they could be equally useful in fetal growth restriction in aiding management. Objective: To determine the efficacy of angiogenic biomarkers at predicting adverse pregnancy outcome in severe early-onset fetal growth restriction. Study design: This is a secondary analysis of the multicentre, placebo-controlled STRIDER UK randomised controlled trial of singleton pregnancies with severe early-onset fetal growth restriction. Women with FGR pregnancies between 22 +0 and 29 +6 weeks of gestation were randomly assigned to receive either sildenafil 25 mg three times daily or placebo until 32 +0 weeks' gestation or delivery. We developed prediction models based upon maternal demographics (age, parity, blood pressure, preeclampsia, gestational hypertension), fetal biometric (estimated fetal weight) and Doppler measurements (Middle Cerebral Artery (MCA), Umbilical Artery (UA)) and maternal angiogenic biomarkers [placental growth factor (PlGF), soluble endoglin (sEng), soluble fms-like tyrosine kinase 1 (sFlt-1) and sFlt-1:PlGF ratio) using both univariate and multivariate analysis. Results: A complete data set was available for 105 of 135 randomised women. Multivariate regression analysis identified estimated fetal weight (EFW) and sFlt-1:PlGF as independent predictors of livebirth (EFW OR: 1.01 (1.008, 1.021); p < 0.001 and lower sFlt-1:PlGF ratio OR: 0.53 (0.284, 0.994); p = 0.048) and overall survival (EFW OR: 1.01 (1.006, 1.015); p < 0.001 and lower sFlt-1/PlGF ratio OR: 0.51 (0.286, 0.904); p = 0.021). EFW was a consistent predictor for all outcomes other than gestation at delivery. sFlt-1:PlGF ratio was a consistent predictor for all outcomes other than neonatal morbidity. Conclusions: In severe early-onset FGR pregnancies livebirth and overall survival can be predicted using a model involving EFW and sFlt-1:PlGF ratio. This model require validation in a larger cohort but may allow informed decision making about pregnancy management, especially in previable cases.